2019
DOI: 10.1038/s41398-019-0570-y
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-related biomarkers in major psychiatric disorders: a cross-disorder assessment of reproducibility and specificity in 43 meta-analyses

Abstract: Inflammation is a natural defence response of the immune system against environmental insult, stress and injury, but hyper- and hypo-inflammatory responses can trigger diseases. Accumulating evidence suggests that inflammation is involved in multiple psychiatric disorders. Using inflammation-related factors as biomarkers of psychiatric disorders requires the proof of reproducibility and specificity of the changes in different disorders, which remains to be established. We performed a cross-disorder study by sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
227
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(235 citation statements)
references
References 71 publications
4
227
0
4
Order By: Relevance
“…Furthermore, the role of inflammation in depression is now supported by a wealth of evidence. Experts now believe that inflammatory processes underlie and contribute to depressive pathophysiology in a significant proportion of cases (68)(69)(70)(71). These concepts grew from observations that medications which reduced inflammatory processes had antidepressant properties.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the role of inflammation in depression is now supported by a wealth of evidence. Experts now believe that inflammatory processes underlie and contribute to depressive pathophysiology in a significant proportion of cases (68)(69)(70)(71). These concepts grew from observations that medications which reduced inflammatory processes had antidepressant properties.…”
Section: Inflammationmentioning
confidence: 99%
“…Briefly, cytokines are elevated in a portion of patients suffering from depression. In particular, tumor necrosis factor alpha (TNFa), interleukin-2 (IL-2), interleukin-6 (IL-6), interleukin-13 (IL-13), interleukin-18 (IL-18), Creactive protein (CRP), chemokine-2 (CCL2), and chemokine-11 (CCL11) are elevated in depression based on multiple metaanalyses (68,71,73). But how inflammatory cytokines induce depressive symptoms remain incompletely understood.…”
Section: Inflammationmentioning
confidence: 99%
“…While promising studies have begun to identify subpopulations of patients with MDD likely to respond to anti-inflammatory therapy (15), results of immune phenotyping in other disorders have been variable. A recent systematic review found that meta-analyses for MDD, ASD, bipolar disorder, and schizophrenia have consistently reported changes in only 16, 7, 8, and 7 individual inflammation-related factors in peripheral blood, respectively (16). The single metaanalysis of immune phenotyping studies in OCD was filtered out because of insufficient statistical power (16).…”
Section: Measuring Inflammation In the Brain And Periphery: Beyond Pomentioning
confidence: 99%
“…A recent systematic review found that meta-analyses for MDD, ASD, bipolar disorder, and schizophrenia have consistently reported changes in only 16, 7, 8, and 7 individual inflammation-related factors in peripheral blood, respectively (16). The single metaanalysis of immune phenotyping studies in OCD was filtered out because of insufficient statistical power (16). Longitudinal data were lacking and state versus trait markers difficult to distinguish, markers were restricted to a few per study based on a biased candidate gene/cytokine approach, and the contribution of confounding factors-including childhood adversity, diet, and smoking-was potentially significant (16).…”
Section: Measuring Inflammation In the Brain And Periphery: Beyond Pomentioning
confidence: 99%
See 1 more Smart Citation